Constitutive overexpression of EPSPS by gene duplication is involved in glyphosate resistance in Salsola tragus. Issue 3 (15th November 2022) - Yanniccari, Marcos; Palma‐Bautista, Candelario; Vázquez‐García, José Guadalupe; Gigón, Ramón; Mallory‐Smith, Carol Ann; De Prado, Rafael
Abstract: BACKGROUND: Glyphosate‐resistant Salsola tragus accessions have been identified in the USA and Argentina; however, the mechanisms of glyphosate resistance have not been elucidated. The goal of this study was to determine the mechanism/s of glyphosate resistance involved in two S. tragus populations (R1 and R2) from Argentina. RESULTS: Both glyphosate‐resistant populations had a six‐fold lower sensitivity to glyphosate than the S population (i.e. resistance index). No evidence of differential absorption, translocation or metabolism of glyphosate was found in the R1 and R2 populations compared to a susceptible population (S). No 5‐enolpyruvylshikimate‐3‐phosphate synthase ( EPSPS ) mutations were detected, but S. tragus R1 and R2 plants had ≈14‐fold higher EPSPS gene relative copy number compared to the S counterpart. In R1 and R2, EPSPS duplication entailed a greater constitutive EPSPS transcript abundance by approximately seven‐fold and a basal EPSPS activity approximately three‐fold higher than the S population. CONCLUSION: The current study reports EPSPS gene duplication for the first time as a mechanism of glyphosate resistance in S. tragus populations. The increase of glyphosate dose needed to kill R1 and R2 plants was linked to the EPSPS transcript abundance and level of EPSPS activity. This evidence supports the convergent evolution of the overexpression of the EPSPS gene in several Chenopodiaceae/Amaranthaceae species adapted to drought environments and the role of gene duplication as an adaptive advantage for plants to withstand stress. © 2022 Society of Chemical Industry. Abstract : Glyphosate‐resistant Salsola tragus populations had 14‐fold higher EPSPS gene relative copy number, seven‐fold greater constitutive EPSPS transcript abundance and three‐fold higher EPSPS activity than a susceptible population.